N-heterocyclic carbene complexes of silver and gold as novel tools against breast cancer progression. (December 2016) - Saturnino, Carmela; Barone, Ines; Iacopetta, Domenico; Mariconda, Annaluisa; Sinicropi, Maria Stefania; Rosano, Camillo; Campana, Antonella; Catalano, Stefania; Longo, Pasquale; Andò, Sebastiano
Aim: Metal carbenic complexes have received considerable attention in both the catalysis and biological fields for their potential applications in cancer and antimicrobial therapies.Results: A small series of new silver and gold N-heterocyclic carbene complexes has been designed and synthesized. Among the tested complexes, one compound was particularly active in inhibiting anchorage-dependent and -independent breast cancer proliferation, and inducing cell apoptosis via a mitochondria-related process. The antitumor activity was associated to the transcriptional activation of the tumor suppressor gene p53 in an Sp1-dependent manner, as evidenced by biological and docking studies.Conclusion: Our results highlight the importance and the versatility of N -heterocyclic carbene complexes of gold and silver as useful tools against breast cancer progression.